Capacity to consent to or refuse psychiatric treatment: an analysis of South African and UK law. Issue 3 (1st September 2016) - Davidson, Laura
Abstract: This article is an analysis of the law on capacity to consent to or refuse psychiatric treatment in South Africa and the UK. The two countries deal with capacity issues in very different ways. In contrast to South Africa's more recent Mental Health Care Act 2002, the UK's Mental Health Act 1983 was drafted in an era of paternalism and risk aversion. Instead of replacing the 1983 Act with a more rights-focused, Act, however, the UK chose to legislate in the form of the Mental Capacity Act 2005. Unfortunately its remit largely excludes psychiatric patients, with the Act's Code of Practice advocating circumvention of advance capacitous decisions by psychiatric patients. The 2005 Act can be contrasted with South Africa's approach to capacity, where the test for consent to treatment is common law based, rather than statutory. In view of the age of the respective Acts, South Africa's legislative framework for mental health might be expected to be significantly more libertarian and compliant with international best practice and human rights law than its British counterpart. Although treatment without consent cannot be provided under the Mental Health Care Act 2002 unless a person either provides consent or lacks the requisite capacity, the balance clearly is in favour of treatment. In the UK, too, enforced treatment is the norm rather than the exception. A detailed critique of the two different approaches taken to matters of legal incapacity is undertaken, involving an examination of each country's test for assessing a civil psychiatric patient's capacity to consent to or refuse health care and treatment. The article also considers how far and to what degree the two Acts might be considered compatible with international law, and in particular the Convention on the Rights of Persons with Disabilities, given the UN's General Comment 1 on art 12.